PENERAPAN ALGORITMA C4.5 UNTUK PENENTUAN JURUSAN SISWA SEKOLAH MENENGAH ATAS - Koko Handoko; Pastima Simanjuntak; Ellbert Hutabri; Erlin Elisa (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Specialization is a process that is carried out at the high school level in the form of a specialization in science and social studies, the purpose of which is for students to receive education according to their interests and abilities. If majoring is done manually it is not effective and efficient so that students do not get the lessons and interests that are in accordance with those taken during the major. The purpose of this research is to help high school (SMA) level students in determining the major they will choose so that they can overcome the problem of confusion that often occurs. The problem of choosing a major is solved by utilizing data mining with the C4.5 method which will produce a decision tree in the form of a suitable major for students to choose from. The results of implementing the C4.5 algorithm can help schools in Batam determine the direction of students to get the right education in high school. From the results of this study, the prediction accuracy of student majors was obtained with a value of 83.33% and a precision of 92.31%.